Different fabrication techniques of implant-supported prostheses - Silas Monteiro Borges; Stephanie Francoi Poole; Izabela Cristina Maurício Moris; Aloísio Oro Spazzin; Adriana Cláudia Lapria Faria; Erica Alves Gomes (Universidade Estadual de Campinas, 2019)
Aim: This study evaluated the mechanical behavior of implant-supported crowns obtained by different fabrication technique after thermomechanical cycling. Methods: Thirty-two external hexagon dental implants were divided into four groups (n=10): CC - conventional casting with torch; EI - electromagnetic induction casting; PL - plasma casting; and CAD-CAM - milling through computer-aided design and computer-aided manufacturing. Vickers microhardness of the specimens were made before and after the thermomechanical cycling, and then subjected to fracture load. Fracture pattern was evaluated. Results: No significant difference was observed comparing the microhardness before and after thermomechanical cycling. CAD-CAM group presented significant lower microhardness than the other groups. No significant statistical difference was showed on fracture load between the groups. The CAD-CAM and PL presented lower number of failure by plastic deformation. Conclusion: The manufacturing techniques affected the mechanical behavior and the failure pattern of implant-supported crowns tested.